An analysis of the auditor's uncertainty about probabilities* - LARSSON, S.; CHESLEY, G. R. (Contemporary Accounting Research, 1986)
Abstract. Uncertainty or ambiguity about what specific probability to associate with a given event is a problem for auditors and is one that has been shown to influence the decisions of others. While some theories of probability assume this problem away, others have tried to address it in various ways. This paper provides a formal analysis of this question and presents a means of characterizing the ambiguity associated with the probability inference. The measure we present can capture a number of the previously specified approaches to this question while exhibiting some very intuitive conclusions and some well‐known mathematical properties. Résumé. L'incertitude ou l'ambiguïté relative à la probabilité spécifique à attribuer à un événement donné, est un problème pour les vérificateurs et un problème qui a été démontré comme influençant les décisions des autres. Alors que certaines théories de probabilité ne tiennent pas compte de ce problème, d'autres ont essayé de s'y intéresser de différentes façons. Cet article fournit une analyse formelle de cette question et présente un moyen de caractériser l'ambiguïté associée avec l'inférence de probabilité. La mesure que nous présentons reprend un certain nombre des approches déjà existantes sur cette question tout en exposant quelques conclusions très intuitives et quelques propriétés mathématiques bien connues.